2016
DOI: 10.1080/02757540.2016.1177520
|View full text |Cite
|
Sign up to set email alerts
|

Copper ecotoxicology of marine algae: a methodological appraisal

Abstract: The production of accurate and reliable data on copper ecotoxicology of marine algae depends on the use of trace metal clean techniques during experimentation. We reviewed the methodologies used in the literature on copper ecotoxicology of marine macro-and microalgae, specifically the use of trace metal clean procedures such as the labware used (glassware vs. plasticware), methods of cleaning the labware (acid soaking and ultrapure water rinsing), stock solution preparation (copper source and acidification), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…In addition, only approximately 70% of the data used for the marine ambient water criteria derivation in the US Environmental Protection Agency guideline (2016) reported measured [dCu T ] in the test treatments. Given the importance of ecotoxicological bioassays in setting ecological standards of metal pollutants to protect and conserve aquatic ecosystems, the present data indicate the importance of adherence to current guidelines of standardized toxicity tests and data reporting (Leal et al 2016).…”
Section: Effect Of [Dcu T ] On Cu Mass Balancementioning
confidence: 86%
See 3 more Smart Citations
“…In addition, only approximately 70% of the data used for the marine ambient water criteria derivation in the US Environmental Protection Agency guideline (2016) reported measured [dCu T ] in the test treatments. Given the importance of ecotoxicological bioassays in setting ecological standards of metal pollutants to protect and conserve aquatic ecosystems, the present data indicate the importance of adherence to current guidelines of standardized toxicity tests and data reporting (Leal et al 2016).…”
Section: Effect Of [Dcu T ] On Cu Mass Balancementioning
confidence: 86%
“…The criteria for guideline derivation of the Organisation for Economic Co‐operation and Development (OECD) and the Australian and New Zealand Environment and Conservation Council (ANZECC) now require bioassay results to be based on measured concentrations, meaning that ecotoxicological studies have to routinely measure and report actual concentrations of a test substance at the start and the conclusion of the exposure (Leal et al ; Warne et al ) to ensure the validity of the toxicity test. Yet, ecotoxicological studies which abide by trace metal–clean protocols and follow current guidelines for the testing of chemicals during bioassays are still mostly lacking (e.g., Maienthal and Becker ; Benoit et al ; Leal et al ). According to Leal et al (), only approximately 25% of toxicity studies regarding marine algae reported actual Cu levels measured in the culture media.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample analysis for sulfide was conducted on board. Equipment and sample bottles used for total dissolved trace metals, Hg T and Cu speciation analysis had been cleaned according to conventional trace metal clean protocols (Sander et al 2009;Leal et al 2016).…”
Section: Sample Collection and Sampling Proceduresmentioning
confidence: 99%